2021
DOI: 10.1007/s40195-021-01242-0
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Electromagnetic Fields and Forced Flow and Their Relevance to the Grain Refinement in Al–Si Alloy Under the Application of Pulsed Magneto-Oscillation

Abstract: Distributions of electromagnetic fields and induced forced flow inside a metal melt are crucial to understand the grain refinement of the metal driven by pulsed magneto-oscillation (PMO). In the present study, PMO-induced electromagnetic fields and forced flow in Ga-20wt%In-12wt%Sn liquid metal have been systematically investigated by performing numerical simulations and corresponding experimental measurements. The numerical simulations have been confirmed by magnetic and melt flow measurements. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The numerical simulation-aided process design for continuous casting is particularly important, and great progress has been made in numerical simulation of PMO in recent years. [23][24][25][26] Gong et al [27] obtained the relationship between electromagnetic force and critical nucleation radius by simulating the electromagnetic field and flow field in the molten metal and combining it with theoretical calculations. Xu et al [25,26] measured the melt flow rate by an ultrasound Doppler velocimetry, and verified the numerical simulation of the flow field of Ga-In-Sn liquid metal treated by PMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical simulation-aided process design for continuous casting is particularly important, and great progress has been made in numerical simulation of PMO in recent years. [23][24][25][26] Gong et al [27] obtained the relationship between electromagnetic force and critical nucleation radius by simulating the electromagnetic field and flow field in the molten metal and combining it with theoretical calculations. Xu et al [25,26] measured the melt flow rate by an ultrasound Doppler velocimetry, and verified the numerical simulation of the flow field of Ga-In-Sn liquid metal treated by PMO.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Gong et al [27] obtained the relationship between electromagnetic force and critical nucleation radius by simulating the electromagnetic field and flow field in the molten metal and combining it with theoretical calculations. Xu et al [25,26] measured the melt flow rate by an ultrasound Doppler velocimetry, and verified the numerical simulation of the flow field of Ga-In-Sn liquid metal treated by PMO. By simulating the electromagnetic and flow fields within the melt under the combined magnetic field formed by PMO and a static magnetic field, Zhu et al [28] observed a single-loop structure in the melt flow parallel to the static magnetic field and a double-loop structure in the melt flow perpendicular to the static magnetic field.…”
Section: Introductionmentioning
confidence: 99%